An Emergency Department Intervention to Increase Warfarin Use for Atrial Fibrillation - Skolarus, Lesli E. (2012)
BACKGROUND: Emergency Department (ED) encounters represent lost opportunities to facilitate anticoagulation for stroke prevention in atrial fibrillation (AF). However, screening of warfarin eligibility in the ED may not be feasible. Thus, we evaluated whether a practical quality improvement (QI) initiative increased post-discharge warfarin use in ED patients with AF. METHODS: This quasi-experimental study was conducted in a single academic health system. Eligible subjects were consecutive patients with AF identified by EKG during an ED evaluation, who were discharged from the ED or the subsequent hospitalization off warfarin. The study consisted of data collection during two time periods: 1) pre-intervention (10/2009 - 4/2010), serving as a baseline, and 2) intervention (6/2010 - 12/2010). The intervention consisted of a mailing to the subjects and their primary care physicians. The primary outcome was the proportion of subjects taking warfarin 1 month following ED presentation. Differences between the proportion of pre-intervention and intervention subjects taking warfarin and warfarin or aspirin were compared with χ(2) tests. RESULTS: At 1 month, 111/204 (55%) of the eligible pre-intervention and 90/160 (56%) of the eligible intervention group patients participated. There was no difference between the pre-intervention and intervention groups in the proportion of subjects taking warfarin at one month (12% vs. 9%, p=0.54), or the proportion of subjects taking either aspirin or warfarin at 1 month (72% vs. 75%, p=0.59). CONCLUSIONS: This practical stroke prevention QI initiative was not associated with an increase in warfarin use among ED patients with AF.